Enunciação proverbial : a inscrição de subjetividade e suas relações na constituição dos sentidos - Santa Clara, Vera Lucia (2012)
Having as focus the proverbial enunciation as a strategy of production of subjectivities we aim at highlighting the articulatory movements that establish onto and though proverbial intertextuality by pointing out, in this articulation, to a strategy where the subject is revealed in opposition to the thesis that there is no subjectivity in a proverb. The evidence of the subjectivity presence in a proverb enunciation can be seen in the everyday practice of language, especially in spontaneous speech interlocution. The importance of proverbial expressions as interaction producers, in any situation of use, is a fact over which there should be no questioning, given the enunciative functionality that characterizes these concise forms of expression. The possibility of image composition to the enunciator is also another element that one can attribute to its use, for the popular wisdom status and its “poetic” and familiar form. This strategy is observed with propriety in narrative texts for a structure characterization that allows better work on established dialogs inserted by proverbial voice, setting an ambiance natural compatibility that exempts alterity indication canonical forms. This articulation process produces inner enunciation movements that reflect on the text dynamics. The text analysis showed a picture of uncommon proverbial occurrences in other enunciative situations, reinforcing the compatibility and complicity thesis among interlocutors as a premise for its use. The supporting theories to this investigation derive from the Theory of Enunciation and are backed by the concepts of enunciative subjectivity proposed by Benveniste in dialog with concept of dialogic interaction and polyphony postulated by Bakhtin.